Additively Manufactured Surgical Implant Guides: A Review. (21st March 2022) - Elliott, Tom; Hamilton, Adam; Griseto, Neil; Gallucci, German O
Abstract: Static computer assisted implant surgery (s‐CAIS) is an integral part of the digital workflow in implant dentistry and provides the link between the virtual planning environment and surgical field. The accuracy of s‐CAIS is influenced by many cumulative factors including the fit of the template which is related to the manufacturing process. This critical review provides an overview of the current research on additively manufactured surgical implant guides.